Behavioral framing and consumer acceptance of new food technologies: Factors influencing consumer demand for active packaging. Issue 1 (4th November 2022) - Just, David R.; Goddard, Julie M.
Abstract: We examine consumer willingness to pay (WTP) for foods packaged using active packaging which can be used to improve quality, shelf life, or safety of a range of products, potentially reducing the use of food additives (preservatives) and food waste. We administer an experimental survey of US food consumers ( n = 2325) with five treatments. The surveys include contingent valuation exercises to assess consumer WTP for six products in active packaging relative to conventional packaging. We find that consumer acceptance of this technology is dependent on the product packaged and related directly to the specific relative benefit. In addition, consumer WTP is impacted by the framing of the technology in relation to other available technologies, information about the developer of the technology, and the degree of specificity of information regarding benefits. Notably, impacts of framing and use cases are primarily apparent among those who are resistant to the technology. A cluster analysis finds that those more likely to resist the technology include households that are lower income, less educated, and more likely to be white [EconLit citations: Q18, M31, D12, D83].